TEBUCONAZOLE: A NEW TRIAZOLE FUNGICIDE MOLECULE FOR THE MANAGEMENT OF STEM ROT OF GROUNDNUT CAUSED BY SCLEROTIUM ROLFSII - GURURAJ SUNKAD (The Bioscan, 2012)
The bio-efficacy of formulations of tebuconazole 2% DS was evaluated for the management of stem rot of groundnut and its effect on dry pod yield. Application of tebuconazole 2%DS @ 1g/kg seed to groundnut kernels prior to sowing was found to be highly effective in the management of stem rot of groundnut with least disease incidence (7.31%) with higher pod yield (2664 kg/ha) and benefit cost ratio (5.42). The fungicide was also very effective in farm and large scale demonstration trials in controlling the stem rot and also resulted higher percent increase in yield (9.95%) over recommended fungicide carbendazim (3g/kg seed). Hence, seed treatment of tebuconazole 2%DS @ 1g/kg seed has been recommended and included in the university package of practices of University of Agricultural Sciences, Raichur, Karnataka for the farmers of region to manage the disease.